Pengembangan Sistem Informasi Monitoring Pekerjaan Kantor Konsultan Pajak Berbasis Web pada Kantor Konsultan Pajak I Gede Arianta - Diago Ariesandika; Satrio Agung Wicaksono; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tax consultant office I Gede Arianta is an office that provides professional services of calculation, depositing and reporting for various types of taxation. At this office one client has one staff member responsible for directing and advising on the case at hand. There are problems in the office such as client data storage is not available centrally, consultation activities difficult to be monitored by the leadership, taxation activities undertaken by staff not validated and difficult to be monitored by the leadership, there is no standard of making a receipt of client documents. Based on the issues, developed the information monitoring system of the tax consultant office work I Gede Arianta that can be used by the office to manage client data centrally, managing and monitoring consulting activities, managing and validating taxation activities undertaken by staff, manage document handover. Information system development method using waterfall model. System testing is performed using black-box testing and time comparison test. The result of black-box testing is 100% valid, meaning there is no error and the average difference of time before and after the implementation of the information system is 38 minutes.